Adolescents' Emotion Regulation in Daily Life: Links to Depressive Symptoms and Problem Behavior - Silk, Jennifer S.; Steinberg, Laurence; Morris, Amanda Sheffield (Child development, 2003)
This study examined links between emotion regulation and adjustment in a sample of 152 adolescents in Grades 7 (M age = 12) and 10 (M age = 15). Emotion regulation was assessed using the experience sampling method, in which adolescents provided multiple reports about the intensity, lability, and strategies used to regulate negative emotions across 1 week. Adolescents also completed self-report measures of adjustment. Adolescents who reported more intense and labile emotions and less effective regulation of these emotions also reported more depressive symptoms and problem behavior. Responding to negative emotions with disengagement (e.g., denial) or involuntary engagement (e.g., rumination) was less effective in regulating negative affect, and greater use of these strategies was related to higher levels of depressive symptoms and problem behavior.